Development of MPI relaxometer for characterization of superparamagnetic nanoparticles - Irfan, M.; Dogan, N.; Sapmaz, T.; Bingolbali, A. (ELSEVIER, 2021)
This paper presents the design, implementation, and experimental measurements of a custom-made MPI relaxometer to characterize superparamagnetic iron oxide nanoparticles (SPIONs) as a tracer for Magnetic Particle Imaging (MPI). The relaxometer is electromagnetic interference (EMI) shielded and serves as a zero magnetic field MPI scanner at 4.6 kHz, and 9.9 kHz. The post-processing analysis was performed on commercially available Vivotrax, Perimag (R), and Synomag nanoparticles for the evaluation of relaxation time, resolution, frequency spectrum of the odd harmonics up to 20th harmonic, and relative signal strength essential parameters for MPI. Sinusoidal excitation magnetic fields of 5 mT, 10 mT, and 15 mT were respectively applied to assess their implications on the resolution of the samples. Moreover, measurements were performed at two different frequencies (4.6 kHz, 9.9 kHz), and the driving frequency-dependent relaxation time of the magnetic nanoparticles was calculated. Perimag (R) was found to be the highest resolution tracer material at all experimental conditions for MPI scanning. The relative signal strength of the Synomag tracer outperformed other nanoparticles that determine the signal-to-noise ratio (SNR) for MPI.
Keywords: Magnetic particle imaging (MPI); Relaxometer; Superparamagnetic iron oxide nanoparticle; (SPION); Relaxation time; Resolution; Electromagnetic Interference (EMI); RELAXATION; VISCOSITY; Materials Science; Physics